Epstein-Barr Virus-Induced miR-155 Attenuates NF-κB Signaling and Stabilizes Latent Virus Persistence - Lu, Fang (American Society for Microbiology (ASM), 2008)
MicroRNAs have been implicated in the modulation of gene expression programs important for normal and cancer cell development. miR-155 is known to play a role in B-cell development and is upregulated in various B-cell lymphomas, including several that are latently infected with Epstein-Barr virus (EBV). We show here that EBV infection of primary human B lymphocytes leads to the sustained elevation of miR-155 and its precursor RNA, BIC. The EBV-encoded latency membrane protein 1 (LMP1) can partially reconstitute BIC activation in B lymphocytes but not in epithelial cell cultures. LMP1 is a potent activator of NF-κB signaling pathways and is essential for EBV immortalization of B lymphocytes. An inhibitor to miR-155 further stimulated NF-κB responsive gene transcription, and IKKɛ was identified as a potential target of miR-155 translational repression. Remarkably, miR-155 inhibitor reduced EBNA1 mRNA and the EBV copy number in latently infected cells. This suggests that miR-155 contributes to EBV immortalization by modulation of NF-κB signaling and the suppression of host innate immunity to latent viral infection.